Low-Temperature CO Oxidation Over CuO/Co3O4 Catalysts - Hu, Sulin; Cheng, Tao; Zhang, Youjin; Fang, Zhiyong; Han, Kaidong; Gao, Minrui (Asian Journal of Chemistry, 2010)
Copper cobalt composite oxide catalysts have been prepared by co-precipitation method. The prepared samples are characterized by X-ray diffraction, transmission electron microscopy, electron diffraction, X-ray photoelectron spectra and nitrogen adsorption to determine the specific surface areas (SBET). The catalytic activity and stability of samples were investigated for CO oxidation by using a microreactor-GC system. The results indicate that the copper cobalt composite oxide catalysts exhibited obviously higher catalytic activity for CO oxidation than that of individual CuO or Co3O4 with CO total conversion at 80 ºC and their stability was quite well. The catalytic activity of the catalysts prepared by co-precipitation increases by increasing the calcination temperature from 150 to 200 ºC and decreases from 200 to 500 ºC. The effect of the volume of NaOH (2.0 mol/L), ageing time, calcination temperature, calcination time, the molar ratios of copper to cobalt and the specific surface areas on the catalytic activity of the catalysts was investigated in this paper.